2018
DOI: 10.1016/j.gene.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a recombinant Aggregatibacter actinomycetemcomitans RTX toxin in Escherichia coli

Abstract: A leukotoxin (LtxA) that is produced by Aggregatibacter actinomycetemcomitans (Aa) is an important virulence determinant in an aggressive form of periodontitis in adolescents. Understanding the function of this protein at the molecular level is critical to elucidating its role in the disease process. To accomplish genetic analysis of the protein structure and relating these observations to toxin function, we have developed an E. coli expression system for the generation and rapid purification of LtxA. Cloning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…3B and C shows a histogram obtained from 47 LtxA channels recorded under these conditions. A fit of the histogram with a Gaussian function yielded an average single-channel conductance of 1.1 ± 0.3 nS somewhat smaller than that at pH 6.0 (G = 1.2 ± 0.3 nS) [39]. Again we found that the single-channel distribution was quite broad, similar to the conditions at pH 6.0 (Fig.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…3B and C shows a histogram obtained from 47 LtxA channels recorded under these conditions. A fit of the histogram with a Gaussian function yielded an average single-channel conductance of 1.1 ± 0.3 nS somewhat smaller than that at pH 6.0 (G = 1.2 ± 0.3 nS) [39]. Again we found that the single-channel distribution was quite broad, similar to the conditions at pH 6.0 (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Here we demonstrate that LtxA causes changes in lysosomal pH in T lymphocytes, however to a leser extent. The pore-forming properties of LtxA are well established [33,60]. Therefore, we propose that LtxA can cause permeabilization of lysosomal membrane, and possibly other intracellular organelles after the toxin is released from lysosomes.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations